2019
DOI: 10.1111/jfb.13953
|View full text |Cite
|
Sign up to set email alerts
|

It's in the eye of the beholder: visual lateralisation in response to the social environment in poeciliids

Abstract: The social environment offers fish complex information about the quality, performance, personality and other cues of potential mates and competitors simultaneously. It is likely, therefore, that the environmental information regarding the context of mate choice is perceived and processed differently in species and sexes in respect to lateralisation. The present study comparatively assessed visual lateralisation behaviour in response to different social or sexual stimuli in three closely related poeciliid speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 102 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…To our knowledge no such investigations have examined this in the context of fish parental care despite parental care being commonplace in many fish species (Balshine, 2012). Sovrano et al (1999; suggest fish process social stimuli preferentially with their right hemisphere, (Sovrano et al, 1999;Sovrano, 2004) though this directional preference can differ even within the same taxonomic family (Fuss et al, 2019) and between different sexes (Reddon and Balshine, 2010).…”
Section: Laterality and Conspecific Recognitionmentioning
confidence: 99%
“…To our knowledge no such investigations have examined this in the context of fish parental care despite parental care being commonplace in many fish species (Balshine, 2012). Sovrano et al (1999; suggest fish process social stimuli preferentially with their right hemisphere, (Sovrano et al, 1999;Sovrano, 2004) though this directional preference can differ even within the same taxonomic family (Fuss et al, 2019) and between different sexes (Reddon and Balshine, 2010).…”
Section: Laterality and Conspecific Recognitionmentioning
confidence: 99%
“…Therefore, the type of stimulus used, particularly the social stimulus, can affect lateralization. Fuss et al (2019) found a statistically significant left-eye bias for female sailfin mollies and Amazon mollies when viewing a female group stimulus, although no such bias when viewing a single female. While most fish are not thought to recognize their own reflection (Kohda et al, 2019), the lack of visual bias and similar variation in both species of our study could indicate a lack of motivation to perform lateralization for the mirror reflection meant to represent a single female.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, mixed visual lateralization in schooling fish determine the fishes' position within the school and overall school cohesion (Dadda and Bisazza, 2006;Bibost and Brown, 2013). A number of studies using poeciliid species found a clear eye bias, with female poeciliids commonly exhibiting a left-eye bias for conspecific stimuli and a right-eye bias for predator or male stimuli (Bisazza et al, 1997a(Bisazza et al, ,b, 1998(Bisazza et al, , 1999De Santi et al, 2001;Fuss et al, 2019). Therefore, the type of stimulus used, particularly the social stimulus, can affect lateralization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations